MENELISIK ASAS KEADILAN DAN KESETARAAN GENDER DALAM UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA PERSPEKTIF ISLAM - Ikhwanuddin Harahap (Yurisprudentia: Jurnal Hukum Ekonomi, 2016)
Ideally, family should be be “ the safetyhome” for all members of the family. But in fact, there are many violence cases  happened in Indonesia families. So that is why the Government respons the cases by Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga. There are many kinds of violence in family, namely physical violence such as beating, slaping, kick, biting, marital rape, etc., and non- physical violence such as intimidation, threat, terror, etc. This article tries to analysis one of the principles in the Undang-Undang namely justice and gender equalities on Islam perspective.